Preliminary investigations into ostrich mycoplasmas : identification of vaccine candidate genes and immunity elicited by poultry mycoplasma vaccines - Van der Merwe, Elizabeth Frances (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--University of Stellenbosch, 2006.